Odpowiedź :
Odpowiedź:
0,2 * (-3 i 1/4 +1/4) = 1/5 * (-3) = -3/5
2,25 * 3 i 1/5 - 1,3 = 2 i 1/4 * 3 i 1/5 - 1 i 3/10 = 9/4 * 16/5 - 1 i 3/10 =
= 36/5 - 1 i 3/10 = 7 i 1/5 - 1 i 3/10 = 7 i 2/10 - 1 i 3/10 = 6 i 12/10 - 1 i 3/10 =
= 5 i 9/10
1/2 + 1 i 1/2 : 6 = 1/2 + 3/2 * 1/6 = 1/2 + 1/4 = 2/4 + 1/4 = 3/4
2,6 : 0,1 - 0,1 : 1/60 = 26 - 1/10 * 60 = 26 -6 = 20
1 i 1/3 - 2 : (1 - 2/3) = 1 i 1/3 - 2 : (3/3 - 2/3) = 1 i 1/3 - 2 : 1/3 =
= 1 i 1/3 - 2 * 3 = 1 i 1/3 - 6 = 1 i 1/3 - 5 i 3/3 = - 4 i 2/3
1/5 - 1/6 : (2 - 1,8) = 1/5 - 1/6 : 0,2 = 1/5 - 1/6 : 1/5 = 1/5 - 1/6 * 5 =
= 1/5 - 5/6 = 6/30 - 25/30 = -19/30
0,3 - 1,2 : (9/4 · (0,2 - 3/4)) = 0,3 - 1,2 : (9/4 * (1/5 - 3/4)) =
= 0,3 - 1 i 2/10 : (9/4 * (4/20 - 15/20)) = 0,3 - 1 i 1/5 : (9/4 * (-11/20)) =
= 0,3 - 6/5 : (-99/80) = 0,3 - 6/5 * (-80/99) = 3/10 +32/33 =
= 99/330 +320/330 = 419/330 = 1 i 89/330
Ja zamiast kreski zrobiłami znak dzielenia i to wychodzi tak samo
Odpowiedź:
[tex]a)\ \ 0,2\cdot(-3\frac{1}{4}+\frac{1}{4})=0,2\cdot(-3)=-0,6\\\\\\b)\ \ 2,25\cdot3\frac{1}{5}-1,3=\frac{225}{100}\cdot\frac{16}{5}-1,3=\frac{9}{\not4_{1}}\cdot\frac{\not16^4}{5}-1,3=\frac{36}{5}-\frac{13}{10}=\frac{72}{10}-\frac{13}{10}=\\\\=\frac{59}{10}=5\frac{9}{10}[/tex]
[tex]c)\ \ \frac{1}{2}+1\frac{1}{2}:6=\frac{1}{2}+\frac{\not3^1}{2}\cdot\frac{1}{\not6_{2}}=\frac{1}{2}+\frac{1}{4}=\frac{2}{4}+\frac{1}{4}=\frac{3}{4}\\\\\\d)\ \ 2,6:0,1-0,1:\frac{1}{60}=26-0,1\cdot60=26-6=20\\\\\\e)\ \ \dfrac{1\frac{1}{3}-2}{1-\frac{2}{3}}=\dfrac{\frac{4}{3}-\frac{6}{3}}{\frac{3}{3}-\frac{2}{3}}=\dfrac{-\frac{2}{3}}{\frac{1}{3}}=-\frac{2}{3}:\frac{1}{3}=-\frac{2}{\not3}\cdot{\not3}=-2[/tex]
[tex]f)\ \ \dfrac{\frac{1}{5}-\frac{1}{6}}{2-1,8}=\dfrac{\frac{6}{30}-\frac{5}{30}}{0,2}=\dfrac{\frac{1}{30}}{\frac{1}{5}}=\frac{1}{30}:\frac{1}{5}=\frac{1}{\not30_{6}}\cdot{\not5^1}=\frac{1}{6}\\\\\\g)\ \ \dfrac{0,3-1,2}{\frac{9}{4}\cdot(0,2-\frac{3}{4})}=\dfrac{-\frac{9}{10}}{\frac{9}{4}\cdot(\frac{1}{5}-\frac{3}{4})}=\dfrac{-\frac{9}{10} }{\frac{9}{4}\cdot(\frac{4}{20}-\frac{15}{20})}=\dfrac{-\frac{9}{10}}{\frac{9}{4}\cdot(-\frac{11}{20})}=\dfrac{-\frac{9}{10}}{-\frac{99}{80}}=[/tex]
[tex]=\frac{9}{10}:\frac{99}{80}=\frac{\not9^1}{\not10_{1}}\cdot\frac{\not80^8}{\not99_{11}}=\frac{8}{11}[/tex]